La descentralización administrativa en Colombia: un reto inconcluso y un desafío para el posconflicto (2016)
Colombia is a country with a strong centralist tradition since the proclamationof the Constitution of 1886, which was only regulated and brought under controlwith the Constitution of 1991; which established the concepts of administrativedecentralization and autonomy of local authorities. However, despite this, after 25years of being issued, the intention of the Constituency to make a more balancedColombia, when it comes to decision-making power, and closeness to generalpopulation's needs; are still unreached challenges. In this regard, those theoreticalconsiderations aim to show how the absence of the state forces in most remoteareas, the ones far away from the political, economic and social power epicenter,has been one of the direct consequences of the internal armed conflict in our country,which from several points of view, is still an issue for the state considering aneventual post-conflict.